Embryonic Development of Muddy Paper Nautilus, Argonauta hians Lightfoot, 1786, from Andaman Sea, Thailand - Charuay Sukhsangchan; Jaruwat Nabhitabhat (Agriculture and Natural Resources, 2007)
Thirty-three specimens of muddy paper nautilus (Argonauta hians Lightfoot, 1786) were collected from fish market and bycatch of purse seine in Phuket Province, Andaman Sea, Thailand. All specimens were mature females with shells or egg cases with developing eggs inside. Egg capsules were collected for observation from each female. Embryonic developmental stages were observed under the binocular microscope and recorded by digital camera. The average number of eggs from individual was 12,048.3±4,432.2. The size of egg capsule (egg) was 1.06±0.11 millimeters in average length. Embryonic development was observed for 15 stages. Hatchlings were planktonic with approximately 0.6 millimeters mantle length.